Analyzing Fraud Diamond for Detecting Fraud Committed with Religiosity as Intervening Variable: Study in Manufacturing Company’s Managers in East Java - Jaya, I Made Laut Mertha; Ilahiyah, Mar'a Elthaf (Esensi: Jurnal Bisnis dan Manajemen, 2020)
This research was conducted to find out the reasons why a manager commits fraud. Diamond fraud model was used in this research. Religiosity variables are used as intervening variables to determine the effect of religiosity in intervening fraudulent actions among managers of manufacturing companies in East JavaThe data analysis techniques used in this study were descriptive analysis and path analysis. The results of the analysis test in this study resulted in several conclusions, namely the Fraud diamond factor proved to have a significant effect on fraud (Fraud) committed by managers of manufacturing companies in East Java. Meanwhile, Fraud diamond (Incentive) factors proved to have no significant effect on fraud (Fraud) committed by managers of manufacturing companies in East Java. In addition, Religiosity was also not able to interfere strongly with the relationship between Fraud diamond on fraud (Fraud) committed by managers of manufacturing companies in East Java. In conclusion, this result of this research proves that the level of religiosity of a manager is not necessarily able to suppress fraud that is committed in the company.